Neutralizing BDNF and FGF2 injection into denervated skeletal muscle improve recovery after nerve repair. Issue 3 (18th June 2020) - Rink, Svenja; Chatziparaskeva, Christina; Elles, Luisa; Pavlov, Stoyan; Nohroudi, Klaus; Bendella, Habib; Sarikcioglu, Levent; Manthou, Marilena; Dunlop, Sarah; Gordon, Tessa; Angelov, Doychin N.
Abstract: Background: After facial nerve injury and surgical repair in rats, recovery of vibrissal whisking is associated with a high proportion of mono‐innervated neuro‐muscular junctions (NMJs). Our earlier work with Sprague Dawley (SD)/Royal College of Surgeons (RCS) rats, which are blind and spontaneously restore NMJ‐monoinnervation and whisking, showed correlations between functional recovery and increase of fibroblast growth factor‐2 (FGF2) and brain‐derived neurotrophic factor (BDNF) in denervated vibrissal muscles. Methods: We used normally sighted rats (Wistar), in which NMJ‐polyinnervation is highly correlated with poor whisking recovery, and injected the vibrissal muscle levator labii superioris (LLS) with combinations of BDNF, anti‐BDNF, and FGF2 at different postoperative periods after facial nerve injury. Results: Rats receiving anti‐BDNF+FGF2 showed low NMJ‐polyinnervation and best recovery of whisking amplitude. Conclusions: Restoration of target reinnervation after peripheral nerve injury requires a complex mixture of trophic factors with a specific time course of availability for each of them.